Methodological Challenge of the Post-Communist Revolution - Šaulauskas, Marius Povilas (Sociologija. Mintis ir veiksmas, 1999)
The article aims to examine the methodological problems of post-communist revolution research. First, the article begins with a critique of the category of revolution for the analysis of the post-communist reality. Second, the article suggests a notion post-communist revolution as special type of change. It is argued that the post-communist revolution is defined by an intensive and radical but yet ordinary social change, whose orientation has four dimensions: restitutionary, imitative, innovative and continuative.